Optimization of the remote system library and information services of V. I. Vernadskyi National Library of Ukraine (based on marketing research) - Yakovenko Olena; Turovska Lesia (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
The purpose of the article is to highlight methodological aspects, the results of a survey of users of the V. I. Vernadskyi National Library of Ukraine (VNLU), aimed at studying the needs and interest of users in electronic information resources of the remote library and information service system. Methodological basis of the research: system approach, system-structural and comparative analysis, synthesis, monitoring, marketing approach. The scientific novelty consists in the development of methodological principles for studying the information needs of remote users of the scientific library, analytical coverage of the results of the conducted marketing research. Conclusions. The conducted library marketing research made it possible to analyze user requests for various types of electronic products, to summarize their wishes and comments; to determine the criteria of user satisfaction with remote library and information services of the VNLU; compare proposals for balancing the information needs of users with the capabilities of the scientific library.